2017
DOI: 10.15252/embr.201643587
|View full text |Cite|
|
Sign up to set email alerts
|

Structural and functional analysis of the GABARAP interaction motif (GIM)

Abstract: Through the canonical LC3 interaction motif (LIR), [W/F/Y]‐X1‐X2‐[I/L/V], protein complexes are recruited to autophagosomes to perform their functions as either autophagy adaptors or receptors. How these adaptors/receptors selectively interact with either LC3 or GABARAP families remains unclear. Herein, we determine the range of selectivity of 30 known core LIR motifs towards individual LC3s and GABARAPs. From these, we define a GABARAP Interaction Motif (GIM) sequence ([W/F]‐[V/I]‐X2‐V) that the adaptor prote… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
141
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 151 publications
(153 citation statements)
references
References 48 publications
11
141
1
Order By: Relevance
“…For example, the xenophagy receptor NDP52 specifically binds the ATG8 protein LC3C [42], whereas the autophagy adaptor PLEKHM1 prefers to bind a different ATG8, GABARAP [16]. A recent study even revealed GABARAP interaction motif (GIM) that mediates high affinity binding of GABARAP-interacting proteins [25]. Considering that some plant species have over 20 ATG8 isoforms, compared to 6 in humans, it is reasonable to hypothesize that ATG8s directly contribute to functional diversification of selective autophagy pathways in plants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the xenophagy receptor NDP52 specifically binds the ATG8 protein LC3C [42], whereas the autophagy adaptor PLEKHM1 prefers to bind a different ATG8, GABARAP [16]. A recent study even revealed GABARAP interaction motif (GIM) that mediates high affinity binding of GABARAP-interacting proteins [25]. Considering that some plant species have over 20 ATG8 isoforms, compared to 6 in humans, it is reasonable to hypothesize that ATG8s directly contribute to functional diversification of selective autophagy pathways in plants.…”
Section: Discussionmentioning
confidence: 99%
“…ATG8 is composed of four α-helices and four β-strands, with a variable N-terminal extension that mediates the growth of the nascent autophagosome via fusion of ATG8-containing vesicles [19][20][21]. There are multiple ATG8 isoforms in metazoans that appear to be functionally specialized based on interactome analyses [22,23] and a few recent functional studies [24][25][26][27][28]. One emerging view is that ATG8 specialization could form a layer of specificity in selective autophagy pathways in addition to the autophagy cargo receptors.…”
Section: Introductionmentioning
confidence: 99%
“…Another protein, Pleckstrin homology domain‐containing protein family member 1 (PLEKHM1), an effector molecule of Rab7 which contains an LC3‐interacting region (LIR) with a conserved [W/F/Y]‐X1‐X2‐[I/L/V] sequence and a GABARAP‐interacting motif (GIM) ([W/F]‐[V/I]‐X2‐V) sequence, can directly interact with the HOPS complex. This interaction and the presence of the LIR and GIM regions together result in recruitment to the autophagosome, regulating a crucial step in the fusion process by interacting with LC3/GABARAP (McEwan et al , ; Rogov et al , ). Additionally, TECPR1 shows interaction with the Atg12–Atg5 complex and PI3P to promote fusion specificity between autophagosomes and lysosomes.…”
Section: Convergence Of Autophagy and Endocytosismentioning
confidence: 99%
“…In ATG12 the aromatic and hydrophobic residue are spaced far apart in the primary sequence, but brought together in a three-dimensional binding epitope [34]. Furthermore, we are as of yet not able to predict the precise determinants for selective binding to the different ATG8s, as some only bind GABARAPs while others only bind LC3s and some bind all ATG8s with high affinity [21,36].…”
Section: Introductionmentioning
confidence: 99%
“…1). Care should be taken in choosing an appropriate ATG8, as several LIR-containing proteins only bind strongly to either GABARAPs [24,36,39], or LC3A/B [18,26]. Once a LIR motif has been identified, the individual LIRs can also be probed for specificity against the different ATG8s by performing single spot analysis of 20-mers containing the LIR motif followed by separate probing with either GABARAP or LC3B [40] ( Fig.…”
Section: Introductionmentioning
confidence: 99%